Cuprous selenide-selenium doped carbon composite material with egg shell structure and preparation method of cuprous selenide-selenium doped carbon composite material

By using an egg-shell structure of copper selenide-selenium doped carbon composite in aluminum batteries, the problem of volume change and dissolution of active substances in aluminum batteries is solved, and better electrochemical performance and cycles are achieved stability.

CN119306184APending Publication Date: 2025-01-14HUNAN INSTITUTE OF SCIENCE AND TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411453188.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The application of cuprous selenide in aluminum batteries is limited by problems such as dissolution of active substances, large volume changes, and mechanical stress during the cycle. The existing cuprous selenide-carbon composite material preparation technology has limitations and it is difficult to effectively buffer volume expansion. and inhibit the shuttle of active substances.

Method used

The copper selenide-selenium doped carbon composite material and its preparation method are used to immerse commercial copper powder by saturated asphalt solution, and carbonization is high-temperaturely carbonized to form a copper-carbon intermediate, and then hydrothermal selenization is obtained to obtain selenium Copperselenium-selenium doped carbon composite material, the copper selenide particles are encapsulated in a selenium doped carbon shell, buffering volume changes and improving electrochemical properties.

Benefits of technology

The volume change of buffered copper selenide in aluminum batteries is realized, and the electrochemical performance is enhanced, especially in the field of electrochemical energy storage and conversion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306184A_ABST
    Figure CN119306184A_ABST
Patent Text Reader

Abstract

The invention relates to an egg shell structure cuprous selenide-selenium doped carbon composite material and a preparation method thereof, and belongs to the technical field of nano functional materials. The preparation method comprises the following steps: by taking commercial copper powder and asphalt as raw materials, firstly coating the commercial copper powder with the asphalt, and then carrying out high-temperature carbonization on a copper-asphalt precursor to obtain a copper-carbon intermediate; the preparation method comprises the following steps: preparing a copper-carbon intermediate, partially etching the copper-carbon intermediate to obtain an egg-shell structure copper-carbon intermediate, and finally performing hydrothermal selenylation to simultaneously realize selenium doping of asphalt derived carbon and confined growth of copper selenide particles to obtain the egg-shell structure cuprous selenide-selenium doped carbon composite material. The preparation method is simple, the morphology structure of the material is controllable, and the method can be used for large-scale production. In the obtained cuprous selenide-selenium-doped carbon composite material with the egg shell structure, a large cavity exists between cuprous selenide particles and a selenium-doped carbon shell, selenium-doped carbon has electronegativity and has a strong adsorption effect on positive ions, and the composite material has potential application prospects in the fields of metal secondary batteries, electrochemical capacitors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano functional materials, and in particular relates to an eggshell structure cuprous selenide-selenium doped carbon composite material and a preparation method thereof. Background Art

[0002] The development of a sustainable, clean, low-carbon energy economy has led to a growing demand for renewable clean energy. Considering the volatility, intermittency, and periodicity of renewable energy, there is an urgent need to develop low-cost, high-energy-density, and high-safety energy storage batteries. Aluminum batteries are ideal battery systems for large-scale energy storage due to their abundant aluminum resources, low cost, and the non-flammable properties of ionic liquid electrolytes. The positive electrode material is the key to determining the performance of aluminum batteries.

[0003] Transition metal selenides have the advantage of low cost and a unique conversion reaction mechanism that gives them high specific capacity, making them potential positive electrode materials for aluminum batteries. Among them, selenium and copper are highly abundant in the earth, and cuprous selenide is easy to synthesize and inexpensive, making it a good positive electrode material for aluminum batteries. However, the practical application of cuprous selenide in aluminum batteries is limited by problems such as dissolution of active substances, large volume changes, and high mechanical stress during the cycle.

[0004] In order to solve the above problems, the general strategy is to combine cuprous selenide with a carbon matrix to construct a conductive buffer network to reduce volume expansion and mechanical stress. The carbon matrix can maintain the structural integrity of the electrode and improve the conductivity of the electrode. For example, Huo et al. prepared a carbon-coated copper selenide positive electrode material by a two-step hydrothermal method combined with heat treatment, which significantly improved the electrochemical performance of the material [ACS Appl. Energy Mater., 2020, 3, 11445−11455]. The research group of Professor Li Nan of Guangzhou University disclosed a method for preparing a nitrogen-doped carbon material composite cuprous selenide electrocatalyst [application number: CN202210652525.8]. This method first prepares a Cu-ZIF-8 precursor by coprecipitation, and then performs high-temperature carbonization and selenization treatment on it to obtain a nitrogen-doped carbon material composite cuprous selenide electrocatalyst, which exhibits excellent electrocatalytic oxygen reduction performance. Ma et al. used Cu2O nanospheres as templates, and synthesized phosphorus-doped cuprous selenide@carbon hollow nanospheres through selenization, in-situ polymerization of dopamine, and phosphating treatment, which showed excellent sodium storage performance [J. Energy Chem., 2023, 77, 227-238]. Zhu et al. prepared self-supporting nitrogen-rich cuprous selenide@carbon nanofibers, which showed excellent potassium storage performance [Sustainable Energy Fuels, 2020, 4, 2453-2461]. Recently, Chen et al. prepared cuprous selenide@carbon thin films by electrodeposition, which showed excellent Cu in aqueous batteries. 2+Storage performance[Chin. Chem. Lett.,2024, 35, 108698].

[0005] In the application of aluminum batteries, the applicant used mechanical ball milling to synthesize copper selenide in the previous work, revealing the electrochemical reaction mechanism and capacity attenuation mechanism of copper selenide, and proposed the use of nitrogen-doped graphene to modify the diaphragm to inhibit the shuttle effect of active components, significantly improving the cycle stability [Chem. Eng. J., 2021, 421, 127792]. Furthermore, the applicant team prepared cuprous selenide nanosheets through precipitation and hydrothermal selenization steps, clarified the electrochemical reaction mechanism and capacity attenuation mechanism of cuprous selenide materials, and proposed the use of acetylene black to modify the diaphragm to inhibit the shuttle effect of active components, significantly improving the cycle stability [Electrochim. Acta, 2023, 466, 143050].

[0006] Therefore, in order to enrich the preparation methods of cuprous selenide-carbon composite materials and further improve the electrochemical properties of cuprous selenide materials in aluminum batteries, an eggshell structured cuprous selenide-selenium-doped carbon composite material, which can effectively buffer the volume expansion of cuprous selenide materials and inhibit the shuttling of active substances, and a preparation method thereof are proposed to solve the above technical problems. Summary of the invention

[0007] In view of the limitations of the existing preparation technology of cuprous selenide-carbon composite materials, the purpose of the present invention is to provide an eggshell structure cuprous selenide-selenium doped carbon composite material and a preparation method thereof. The method first uses a saturated asphalt solution to impregnate commercial copper powder, and after drying, obtains an asphalt-coated copper powder precursor; the precursor is subjected to high-temperature treatment in a N2 atmosphere, and the carbon layer generated by asphalt carbonization in situ coats the copper particles to obtain a copper-carbon intermediate; then the copper-carbon intermediate is partially treated to generate an eggshell structure copper-carbon intermediate; finally, hydrothermal selenization is performed to obtain an eggshell structure cuprous selenide-selenium doped carbon composite material, which aims to solve the problems of large volume change and active material dissolution in the application of existing cuprous selenide materials in aluminum batteries. In the eggshell structure cuprous selenide-selenium doped carbon composite material obtained by the present invention, there is a large cavity between the cuprous selenide particles and the selenium doped carbon shell, which can buffer the volume change of cuprous selenide. In addition, selenium-doped carbon has negative electronegativity and has a strong adsorption effect on cations, so the composite material exhibits good electrochemical performance in aluminum batteries.

[0008] To achieve the above object, the present invention provides a method for preparing an eggshell structure cuprous selenide-selenium-doped carbon composite material, which comprises the following steps: Step 1: Mix excess asphalt with an organic solvent, heat and reflux for 2 to 6 hours; after cooling to room temperature, separate the lower layer solution, which is the asphalt saturated solution; Step 2: Mix the copper powder with the asphalt saturated solution obtained in step 1, and put it into an oven for drying to obtain a copper-asphalt precursor; Step 3: placing the copper-asphalt precursor obtained in step 2 in a horizontal tube furnace for high-temperature carbonization to obtain a copper-carbon intermediate; Step 4: Mix the copper-carbon intermediate obtained in step 3 with an etchant, stir, filter, wash, and dry to obtain an eggshell structure copper-carbon intermediate; Step 5: Mix the eggshell structure copper-carbon intermediate obtained in step 4 with selenium powder, add the mixture into hydrazine hydrate and stir it thoroughly, and finally transfer it to a hydrothermal reactor, seal it, heat it to the target temperature, and then keep it warm for reaction. After the reaction is completed, cool it naturally, filter, wash it, and dry it to obtain an eggshell structure cuprous selenide-selenium-doped carbon composite material.

[0009] Preferably, in step 1, the asphalt is any one of coal tar asphalt, petroleum asphalt, and natural asphalt, the organic solvent is any one of carbon disulfide and carbon tetrachloride, the reflux temperature is 50 to 80° C., and the reflux time is 2 to 6 hours.

[0010] Preferably, in step 2, the amount of copper powder is 0.1 g to 1.0 g, specifically 0.1 g, and the volume of the saturated asphalt solution is 10 mL to 50 mL, specifically 15 mL.

[0011] Preferably, in step 3, the protective gas is any one of N2 and Ar, specifically N2, and the carbonization temperature is 400-1000 ℃ First, heat up to 300 ~ 400 ℃ Keep warm for 1 to 2 hours, specifically 400 ℃ Keep warm for 1 hour, then raise the temperature to 700~1000 ℃ Keep warm for 2 to 4 hours, specifically 800℃ for 3 hours.

[0012] Preferably, in step 4, the etchant may be any one of FeCl3 solution and nitric acid, specifically FeCl3 solution, with a concentration of 1 to 3 mol / L, specifically 2 mol / L. The concentration of nitric acid is 1 to 3 mol / L, specifically 3 mol / L. The etching time is 10 to 60 minutes, specifically 40 minutes, and the heating rate is 2 to 5°C / minute, specifically 4°C / minute.

[0013] Preferably, in step 5, the hydrothermal selenization solution is a mixed solution of selenium powder and hydrazine hydrate, the mass concentration of hydrazine hydrate is 50% to 98%, specifically 50%, the mass ratio of the selenium powder to the eggshell structure copper-carbon intermediate is 1:1 to 3:1, specifically 2:1, the mass ratio of the selenium powder to hydrazine hydrate is 1:50 to 1:100, specifically 1:100, the hydrothermal reaction temperature is 160 to 200°C, specifically 200°C, and the reaction time is 12 to 24 hours, specifically 24 hours.

[0014] Disclosed is an eggshell structured cuprous selenide-selenium doped carbon composite material. The eggshell structured cuprous selenide-selenium doped carbon composite material is prepared by the eggshell structured cuprous selenide-selenium doped carbon composite material method. The cuprous selenide particles of the eggshell structured cuprous selenide-selenium doped carbon composite material are encapsulated inside the selenium doped carbon, a large cavity exists between the cuprous selenide particles and the selenium doped carbon shell, and the selenium doped carbon has negative charge and has a strong adsorption effect on cations.

[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation process of the present invention is simple, low-cost, does not require the use of a template, is easy to scale up, and the morphology and structure of the composite material are controllable; (2) In the eggshell structure cuprous selenide-selenium-doped carbon composite material prepared by the present invention, there is a large cavity between the cuprous selenide particles and the selenium-doped carbon shell. The selenium-doped carbon has negative charge and has a strong adsorption effect on cations, and has a very broad application prospect in the field of electrochemical energy storage and conversion. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The XRD spectrum (a) and SEM image (b) of cuprous selenide obtained in Example 1 of the present invention; Figure 2 The SEM images of the copper-carbon intermediate (a), the eggshell structure copper-carbon intermediate (b) and the eggshell structure cuprous selenide-selenium-doped carbon composite material (c) obtained in Example 2 of the present invention are shown; Figure 3 The SEM images of the copper-carbon intermediate (a), the eggshell structure copper-carbon intermediate (b) and the eggshell structure cuprous selenide-selenium-doped carbon composite material (c) obtained in Example 3 of the present invention are shown; Figure 4 The SEM images of the copper-carbon intermediate (a), the eggshell structure copper-carbon intermediate (b) and the eggshell structure cuprous selenide-selenium-doped carbon composite material (c) obtained in Example 4 of the present invention are shown; Figure 5The SEM image (a), bright field TEM image (b), dark field TEM image (c) and element mapping diagram (df) of the eggshell structure cuprous selenide-selenium doped carbon composite material obtained in Example 4 of the present invention; Figure 6 XRD spectra of cuprous selenide and cuprous selenide-selenium-doped carbon composite materials obtained in Examples 1, 2, 3 and 4 of the present invention; Figure 7 This is a graph showing the electrochemical performance of cuprous selenide and cuprous selenide-selenium-doped carbon composite materials obtained in Examples 1, 2, 3 and 4 of the present invention in aluminum batteries. DETAILED DESCRIPTION

[0017] The present invention will be described in more detail through specific embodiments, but the protection scope of the present invention is not limited to these embodiments. Example 1

[0018] Take 0.2 g of selenium powder and dissolve it in 20 mL of hydrazine hydrate (mass fraction is 50%). Under continuous stirring, add 0.1 g of copper powder and 30 mL of deionized water, and continue stirring at room temperature for 30 minutes. Then transfer the mixture to a 100 mL hydrothermal reactor, seal it and put it in an oven, heat it to 200℃ and keep it warm for 24 hours. After cooling, the product is centrifuged, washed with deionized water and ethanol several times, and dried at 60℃ to obtain cuprous selenide. The phase structure of the sample is analyzed by XRD, and the morphology of the sample is characterized by SEM at an accelerating voltage of 10 kV. Figure 1 (a) shows the XRD spectrum of cuprous selenide obtained in this example. Figure 1 (a) It can be seen that the prepared cuprous selenide is a cubic crystal system with sharp diffraction peaks and good surface crystallinity. Figure 1 (b) shows the SEM image of cuprous selenide obtained in this example. Figure 1 (b) It is known that the obtained cuprous selenide presents an irregular block morphology and small crystalline particles. Example 2

[0019] 0.1 g of copper powder and 10 mL of saturated asphalt solution were mixed and placed in an oven at 60°C to dry to obtain a copper-asphalt precursor. The obtained copper-asphalt precursor was placed in a corundum crucible and placed in a horizontal tube furnace. The temperature was raised to 400°C for 1 hour under N2 atmosphere, then raised to 800°C for 3 hours, and then taken out after cooling to obtain a copper-carbon intermediate. The obtained copper-carbon intermediate was mixed with 10 mL of 2 M FeCl3 aqueous solution, stirred at room temperature for 90 seconds, filtered, washed with water, and dried at 60°C to obtain an eggshell structure copper-carbon intermediate. 0.2 g of selenium powder was dissolved in 20 mL of hydrazine hydrate (mass fraction of 50%). Under continuous stirring, the obtained eggshell structure copper-carbon intermediate and 30 mL of deionized water were added, and stirring continued at room temperature for 30 minutes. The mixture was then transferred to a 100 mL hydrothermal reactor, sealed, placed in an oven, and heated to 200°C for 24 hours. After cooling, the product was centrifuged, washed with deionized water and ethanol for several times, and dried at 60°C to obtain cuprous selenide-selenium-doped carbon composite material. The morphology of the sample was characterized by SEM at an accelerating voltage of 10 kV. Figure 2 The SEM images of the copper-carbon intermediate and the cuprous selenide-selenium-doped carbon composite material obtained in this example are shown. Figure 2 It can be seen that the phenomenon of carbon shell damage occurs in the prepared cuprous selenide-selenium-doped carbon composite material. The results of this embodiment show that when the amount of asphalt saturated solution is small, the complete encapsulation of cuprous selenide cannot be achieved. The reason may be that when a small amount of asphalt saturated solution is used, the carbon coating layer of the copper-carbon intermediate formed in the carbonization process is thinner. The subsequent hydrothermal selenization process causes a large volume expansion due to the transformation of copper to cuprous selenide, which in turn causes the carbon coating layer to rupture. Therefore, appropriately increasing the amount of asphalt saturated solution can increase the thickness of the carbon layer, which is expected to achieve the preparation of the target sample. Example 3

[0020] 0.1 g of copper powder and 15 mL of saturated asphalt solution were mixed and dried in an oven at 60°C to obtain a copper-asphalt precursor. The obtained copper-asphalt precursor was placed in a corundum crucible and placed in a horizontal tube furnace. The temperature was raised to 400°C for 1 hour under N2 atmosphere, then raised to 800°C for 3 hours, and then taken out after cooling to obtain a copper-carbon intermediate. The obtained copper-carbon intermediate was mixed with 10 mL of 2 M FeCl3 aqueous solution, stirred at room temperature for 90 seconds, filtered, washed with water, and dried at 60°C to obtain an eggshell structure copper-carbon intermediate. 0.2 g of selenium powder was dissolved in 20 mL of hydrazine hydrate (mass fraction of 50%). Under continuous stirring, the obtained eggshell structure copper-carbon intermediate and 30 mL of deionized water were added, and stirring continued at room temperature for 30 minutes. The mixture was then transferred to a 100 mL hydrothermal reactor, sealed, placed in an oven, and heated to 200°C for 24 hours. After cooling, the product was centrifuged, washed with deionized water and ethanol for several times, and dried at 60°C to obtain cuprous selenide-selenium-doped carbon composite material. The morphology of the sample was characterized by SEM at an accelerating voltage of 10 kV. Figure 3 The SEM images of the copper-carbon intermediate and the cuprous selenide-selenium-doped carbon composite material obtained in this example are shown. Figure 3 It can be seen that no carbon shell damage was observed in the prepared cuprous selenide-selenium-doped carbon composite material, and the cuprous selenide particles were completely encapsulated in the selenium-doped carbon shell, showing a typical eggshell structure. Example 4

[0021] 0.1 g of copper powder and 20 mL of saturated asphalt solution were mixed and dried in an oven at 60°C to obtain a copper-asphalt precursor. The obtained copper-asphalt precursor was placed in a corundum crucible and placed in a horizontal tube furnace. The temperature was raised to 400°C for 1 hour under N2 atmosphere, then raised to 800°C for 3 hours, and then taken out after cooling to obtain a copper-carbon intermediate. The obtained copper-carbon intermediate was mixed with 10 mL of 2 M FeCl3 aqueous solution, stirred at room temperature for 90 seconds, filtered, washed with water, and dried at 60°C to obtain an eggshell structure copper-carbon intermediate. 0.2 g of selenium powder was dissolved in 20 mL of hydrazine hydrate (mass fraction of 50%). Under continuous stirring, the obtained eggshell structure copper-carbon intermediate and 30 mL of deionized water were added, and stirring continued at room temperature for 30 minutes. The mixture was then transferred to a 100 mL hydrothermal reactor, sealed, placed in an oven, and heated to 200°C for 24 hours. After cooling, the product was centrifuged, washed with deionized water and ethanol for several times, and dried at 60°C to obtain cuprous selenide-selenium-doped carbon composite material. The morphology of the sample was characterized by SEM at an accelerating voltage of 10 kV. Figure 4 The SEM images of the copper-carbon intermediate and the cuprous selenide-selenium-doped carbon composite material obtained in this example are shown. Figure 4It can be seen that no carbon shell damage was observed in the prepared cuprous selenide-selenium-doped carbon composite material, and the cuprous selenide particles were completely encapsulated in the selenium-doped carbon shell, showing a typical eggshell structure. Figure 5 The TEM images and element mapping further demonstrated the complete eggshell structure of the composite material, and the main components of the composite material were C, Cu, and Se elements. Figure 6 is the XRD spectrum of the obtained cuprous selenide and composite material. Figure 6 It can be seen that the synthesized material is mainly cubic Cu2Se. Example 5

[0022] A typical coating process was used to prepare a working electrode composed of active material, carbon black and polyvinylidene fluoride in a weight ratio of 6:3:1. The electrolyte was a room temperature ionic liquid electrolyte prepared by anhydrous aluminum chloride and 1-ethyl-3-methylimidazole chloride (molar ratio 1.3:1). High-purity aluminum foil was used as the counter electrode and reference electrode. Glass fiber was used as the diaphragm. The soft-pack battery was assembled in an Ar-filled glove box, and both H2O and O2 were less than 0.1 ppm. At different current densities, the 3+ The electrochemical performance of the battery was tested on a multi-channel battery test system (CT2001A) within the voltage range of 1000A / 2000A.

[0023] This example aims to study the electrochemical performance of cuprous selenide and eggshell-structured cuprous selenide-selenium-doped carbon composite materials as positive electrode materials for aluminum batteries. Figure 7 As shown in a, the eggshell structured cuprous selenide-selenium-doped carbon composite material has a higher reversible specific capacity at different current densities, indicating its excellent rate performance. Figure 7 b is the assembled aluminum battery at 1.0 A g -1 The cycling performance at the current density is given by Figure 7 b It can be seen that the cycle stability of the eggshell structure cuprous selenide-selenium-doped carbon composite material is better than that of cuprous selenide. The above results show that the electrochemical performance of electrode materials can be significantly improved by rationally designing their structure.

[0024] Finally, it should be noted that the above are only preferred embodiments of the present invention, which are easily understood by those skilled in the art and are not intended to limit the present invention. Any simple equivalent changes and modifications made with reference to the contents of the specification of the present invention, as well as any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention, should still fall within the scope of protection of the present invention.

Claims

1. A method for preparing an eggshell structure cuprous selenide-selenium doped carbon composite material, characterized in that: The following steps are involved: Step 1. Preparation of asphalt saturated solution: using asphalt as raw material, adding organic solvent, first heating and refluxing to dissolve, then cooling to room temperature to obtain asphalt saturated solution for standby use; Step 2. Preparation of copper-asphalt precursor: soak the commercial copper powder in the saturated asphalt solution obtained in step 1, and dry it; repeatedly soak the dried copper-asphalt precursor in the saturated asphalt solution obtained in step 1, dry it, and set it aside; Step 3. Preparation of copper-carbon intermediate: using the copper-asphalt precursor obtained in step 2 as a raw material, carbonizing at high temperature in a horizontal tube furnace under a N2 atmosphere, taking it out after cooling, and obtaining a carbide for standby use; Step 4. Preparation of eggshell structure copper-carbon intermediate: partially etch the carbonized product of step 3, wash with water, and dry to obtain an etched product for standby use; Step 5. Preparation of eggshell structure cuprous selenide-selenium-doped carbon composite material: The etching product obtained in step 4 is subjected to hydrothermal selenization treatment to obtain an eggshell structure cuprous selenide-selenium-doped carbon composite material.

2. The method for preparing the eggshell structure cuprous selenide-selenium doped carbon composite material according to claim 1, characterized in that: In step 1, the asphalt is any one of coal tar asphalt, petroleum asphalt, and natural asphalt, the organic solvent is any one of carbon disulfide and carbon tetrachloride, the reflux dissolution temperature is 50 to 80° C., and the reflux dissolution time is 2 to 6 hours.

3. The method for preparing the eggshell structure cuprous selenide-selenium doped carbon composite material according to claim 1, characterized in that: In the step 2, the mass of the commercial copper powder is 0.1 g to 1.0 g, the volume of the saturated asphalt solution is 15 mL to 50 mL, and the number of repeated immersion-drying is 2 to 5 times.

4. The method for preparing the eggshell structure cuprous selenide-selenium doped carbon composite material according to claim 1, characterized in that: In step 3, the carbonization temperature is 400 to 1000 ℃ ; First, heat up to 300-400 ℃ Keep warm for 1 to 2 hours, then raise the temperature to 700 to 1000 ℃ Keep warm for 2 to 4 hours, with a heating rate of 2 to 5°C / min.

5. The method for preparing the eggshell structure cuprous selenide-selenium doped carbon composite material according to claim 1, characterized in that: In step 4, the acid is any one of FeCl3 solution and nitric acid, the concentration of the FeCl3 solution is 1 mol / L to 3 mol / L, the concentration of the nitric acid is 1 mol / L to 3 mol / L, and the etching time is 1 to 3 minutes.

6. The method for preparing the eggshell structure cuprous selenide-selenium doped carbon composite material according to claim 1, characterized in that: In step 5, the hydrothermal selenization solution is a mixed solution of selenium powder and hydrazine hydrate, the mass concentration of hydrazine hydrate is 50% to 98%, the mass ratio of selenium powder to eggshell structure copper-carbon intermediate is 1:1 to 3:1, the mass ratio of selenium powder to hydrazine hydrate is 1:50 to 1:100, the hydrothermal reaction temperature is 160 to 200°C, and the reaction time is 12 to 24 hours.

7. An eggshell structure cuprous selenide-selenium doped carbon composite material, characterized in that: The eggshell structured cuprous selenide-selenium-doped carbon composite material is prepared by the eggshell structured cuprous selenide-selenium-doped carbon composite material method described in any one of claims 1 to 6. The cuprous selenide particles of the eggshell structured cuprous selenide-selenium-doped carbon composite material are encapsulated inside the selenium-doped carbon, and a large cavity exists between the cuprous selenide particles and the selenium-doped carbon shell. The selenium-doped carbon has negative charge and has a strong adsorption effect on cations.

Citation Information

Patent Citations

  • Nitrogen-doped carbon material composite cuprous selenide electrocatalyst as well as preparation method and application thereof

    CN115101753A